2019
DOI: 10.3928/01477447-20191001-01
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Tumor Recurrence, and Function Following Shoulder Girdle Limb Salvage at 24 to 35 Years of Follow-up

Abstract: Limb salvage is the treatment of choice for malignant shoulder girdle tumors; however, there is a paucity of data examining the long-term outcome. The authors have previously reported on a cohort of patients at short- and mid-term follow-up. The purpose of this study was to report the long-term outcome of shoulder reconstruction in terms of oncological and functional outcome. The authors reviewed 53 patients who underwent a limb salvage procedure for treatment of a tumor of the shoulder girdle. At a mean of 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…19,[20][21][22][23][24] Five investigations comparing alternative reconstructive methods detected no significant TESS differences. [25][26][27][28][29] Moreover, Jones highlighted that TESS could not distinguish between resections of the anterior compartment that involved or spared the femoral and sciatic nerves. 30 In contrast, Davidge and Griffin identified that more extensive resections had poorer functional outcomes.…”
Section: Toronto Extremity Salvage Scorementioning
confidence: 99%
“…19,[20][21][22][23][24] Five investigations comparing alternative reconstructive methods detected no significant TESS differences. [25][26][27][28][29] Moreover, Jones highlighted that TESS could not distinguish between resections of the anterior compartment that involved or spared the femoral and sciatic nerves. 30 In contrast, Davidge and Griffin identified that more extensive resections had poorer functional outcomes.…”
Section: Toronto Extremity Salvage Scorementioning
confidence: 99%
“…Endoprostheses and allograft prosthetic composites (APC) have become the mainstay of reconstruction options following resection of a proximal humeral bone tumor 1–14 . These techniques were developed to provide a stable platform for elbow, hand, and wrist function; however, historically shoulder motion and function were limited.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques were developed to provide a stable platform for elbow, hand, and wrist function; however, historically shoulder motion and function were limited. Currently, endoprosthetic reconstruction of the proximal humerus is commonly performed due to its low complication rate, shorter operative times, and ease of reconstruction 1–12 . The reported rate of failure of an upper extremity endoprosthesis or APC is less than 20%, and the most common failure modes include soft‐tissue insufficiency causing subluxation or instability, as well as infection 3,13 …”
Section: Introductionmentioning
confidence: 99%
“…Limb‐salvage surgery is pursued whenever possible for patients with oncologic processes in the upper extremity. Although limb‐salvage surgery is the treatment of choice, it is known to be technically challenging 1–13 . Endoprosthetic replacement of the proximal humerus has become a reconstructive technique of choice due to the low complication rate and the relative ease of reconstruction 4–13 .…”
Section: Introductionmentioning
confidence: 99%
“…Although limb-salvage surgery is the treatment of choice, it is known to be technically challenging. [1][2][3][4][5][6][7][8][9][10][11][12][13] Endoprosthetic replacement of the proximal humerus has become a reconstructive technique of choice due to the low complication rate and the relative ease of reconstruction. [4][5][6][7][8][9][10][11][12][13] The reported rate of failure of an upper extremity endoprosthesis is 17% for any reason, with structural failure (Henderson Type 3; periprosthetic or prosthetic fracture or deficient osseous supporting structure) occurring in 0.84%-1.1% of patients.…”
Section: Introductionmentioning
confidence: 99%